1997
DOI: 10.1038/385540a0
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K-related kinase involved in NF-KB induction by TNF, CD95 and IL-1

Abstract: Several members of the tumour-necrosis/nerve-growth factor (TNF/NGF) receptor family activate the transcription factor NF-kappaB through a common adaptor protein, Traf2 (refs 1-5), whereas the interleukin 1 type-I receptor activates NF-kappaB independently of Traf2 (ref. 4). We have now cloned a new protein kinase, NIK, which binds to Traf2 and stimulates NF-kappaB activity. This kinase shares sequence similarity with several MAPKK kinases. Expression in cells of kinase-deficient NIK mutants fails to stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
915
4
12

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,240 publications
(955 citation statements)
references
References 30 publications
24
915
4
12
Order By: Relevance
“…In the NF-κB activation pathway, IKK complex can induce serine phosphorylation of IκBα and IκBβ [22]. Previous studies suggested the involvement of serine/threonine kinase NIK in phosphorylation and activation of the IKK complex [23]. To determine the roles of NIK, IKKα, IKKβ and IKKγ in C. crepidioides -induced iNOS expression in RAW264.7 cells, plasmids encoding dominant-negative mutants of NIK, IKKα, IKKβ and IKKγ were used.…”
Section: Resultsmentioning
confidence: 99%
“…In the NF-κB activation pathway, IKK complex can induce serine phosphorylation of IκBα and IκBβ [22]. Previous studies suggested the involvement of serine/threonine kinase NIK in phosphorylation and activation of the IKK complex [23]. To determine the roles of NIK, IKKα, IKKβ and IKKγ in C. crepidioides -induced iNOS expression in RAW264.7 cells, plasmids encoding dominant-negative mutants of NIK, IKKα, IKKβ and IKKγ were used.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of NIK potently induces NF-kB (Malinin et al, 1997), primarily through the non-canoncial pathway (Scheidereit, 2006). In addition, some studies have demonstrated that MEKK1 is activated by TNFa and IL-1 and can potentiate the stimulatory effect of TNFa on IKK and NF-kB activation (Hirano et al, 1996;Lee et al, 1998).…”
Section: Inhibitors That Act Upstream Of the Ikk Complexmentioning
confidence: 99%
“…More specifically, NIK can directly phosphorylate IKKa for activation of the non-canonical p52/RelB pathway (see Perkins, 2006;Scheidereit, 2006). As such, overexpression of kinasedeficient NIK mutants can block the ability of IL-1 and TNFa to induce NF-kB (Malinin et al, 1997;Song et al, 1997).…”
Section: Inhibitors That Act Upstream Of the Ikk Complexmentioning
confidence: 99%
“…Once free, unbound NF-kB dimerizes and becomes an active transcription factor that translocates to the nucleus and activates transcription of NFkB-responsive genes. IKKs are phosphorylated by NIK (NF-kB-inducing kinase), a MAP kinase that is part of the TNF-RI receptor complex (reviewed in Gilmore et al, 1996;Malinin et al, 1997). According to this model, TNF-RI activation may stimulate RIP kinase activity, which then phosphorylates NIK, which in turn, activates IKKa and IKKb.…”
Section: Survival Signals Transduced By Tnf-rimentioning
confidence: 99%